German romance, Volume III, Iwein, or, The knight with the lion - Hartmann von Aue 1160-1210 (Arthurian archives, 2023)
Iwein, or The Knight with the Lion, is a free Middle High German adaptation of Chrťien de Troyes' Old French Arthurian romance, Yvain. Written c.1200 by a Swabian knight, Hartmann von Aue, Iwein charts the development towards maturity of a young knight who falls into error, neglecting his hard-won wife by devoting himself excessively to chivalric pursuits. This parallel-text edition, offering the first English translation, is based on one of the two earliest complete manuscripts, Giessen, University Library, no. 97 (Iwein B), dating from the second quarter of the thirteenth century. It contains a large number of lines, particularly in the later stages of the poem, which are not present in the other early manuscript, A (Heidelberg, cpg 397)